A review on wax deposition issue and its impact on the operational factors in the crude oil pipeline - Elganidi, Ibrahim; Elarbe, Basem; Norida, Ridzuan; Norhayati, Abdullah (UTM Press, 2021)
The deposition of wax is a common occurrence affecting the flowability of crude oil, which happens at a temperature beneath the Wax Appearance Temperature. At this threshold, there is a gradual accumulation of crystals wax on the inner surface of pipelines. In this research, the previous studies on the effects of residence time, pressure, flow rate, crude oil composition, and temperature differential were carefully enumerated. On the overall, the differential temperature across the pipeline wall and crude oil inside it were considered as the most critical factor contributing to wax deposition. The result from different studies had argued out the effect of significant temperature differential as a leading cause of wax deposition reduction. Also, there is conflict among many researchers on whether the flow rate could result in a reduction in the amount and thickness of deposited wax. However, the wax deposition increases with an increasing resident time up to a particular time, after which the wax deposition experiences a downward trend. On the contrary, most researchers indicated that pressure is not a significant factor of wax deposition, but the conclusion that obtained through this research shows the opposite. Despite these, additional works are required in acquiring substantial results for more accurate as compared with the real-life crude oil flow in the pipeline.